Increased IKKϵ protein stability ensures efficient type I interferon responses in conditions of TBK1 deficiency - Wegner, Julia; Hunkler, Charlotte; Ciupka, Katrin; Hartmann, Gunther; Schlee, Martin (Frontiers in Immunology, 2023)
TBK1 and IKKϵ are related, crucial kinases in antiviral immune signaling pathways downstream of cytosolic nucleic acid receptors such as cGAS and RIG-I-like receptors. Upon activation, they phosphorylate the transcription factors IRF3 and IRF7 and thereby initiate the expression of type I interferons and antiviral effectors. While point mutation-induced loss of TBK1 kinase activity results in clinical hyper-susceptibility to viral infections, a complete lack of TBK1 expression in humans is unexpectedly not associated with diminished antiviral responses. Here, we provide a mechanistic explanation for these so-far unexplained observations by showing that TBK1 controls the protein expression of its related kinase IKKϵ in human myeloid cells. Mechanistically, TBK1 constitutively diminishes the protein stability of IKKϵ independent of TBK1 kinase activity but dependent on its interaction with the scaffold protein TANK. In consequence, depletion of TBK1 protein but not mutation-induced kinase deficiency induces the upregulation of IKKϵ. Due to the functional redundancy of the kinases in cGAS-STING and RIG-I-like receptor signaling in human myeloid cells, enhanced IKKϵ expression can compensate for the loss of TBK1. We show that IKKϵ upregulation is crucial to ensure unmitigated type I interferon production in conditions of TBK1 deficiency: While the type I interferon response to Listeria monocytogenes infection is maintained upon TBK1 loss, it is strongly diminished in cells harboring a kinase-deficient TBK1 variant, in which IKKϵ is not upregulated. Many pathogens induce TBK1 degradation, suggesting that loss of TBK1-mediated destabilization of IKKϵ is a critical backup mechanism to prevent diminished interferon responses upon TBK1 depletion.